Evaluating the Performance of LPG 3 KG Filling Machines: An ANOVA Approach to Machine Brand Efficiency (Study case: SPBE Wilayah Sumatera Utara-SAR Medan PT Pertamina Patra Niaga C&T). - Yati, Nurhayati; Arisman; Simbolon, Hasanal Fachri Satia; Simatupang, Baharis Setia Adisahputra; Simangunsong, Pandi Barita Nauli (Cattleya Darmaya Fortuna, 2025)
This study aims to investigate the differences in the average loading order quantities during the LPG 3 Kg filling process, as influenced by the type of filling machine brand. Specifically, the research focuses on three brands of filling machines: KOSAN-215H, DAESUNG-2189, and ELIXIR-217Q, which are utilized at the LPG Filling Stations (SPBE) in the Sumatera Utara-SAR Medan PT Pertamina Patra Niaga C&T. The statistical method employed for analysis is One-Way Univariate Analysis of Variance (ANOVA). A total of 27 observations were collected for each machine brand. The results of the analysis show that the calculated F-Statistic (3.171240679) exceeds the F-Critical (3.11379226), with a P-value of 0.0474111978, which is < 0.05 significance threshold. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted, indicating that there is a statistically significant difference in the average loading order quantities among the three filling machines. These findings suggest that the loading order quantities differ significantly across the different brands of 3 KG LPG filling machines.